2022
DOI: 10.1109/access.2022.3175585
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Electric Vehicle Development, Deployment, and Policy Initiatives to Reduce GHG Emissions: Opportunities and Challenges

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…e Simulated Allocation (SAL) algorithm was designed in [10] to minimize the communication power and latency during the mapping process. However, the designed algorithm failed to consider the network throughput.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…e Simulated Allocation (SAL) algorithm was designed in [10] to minimize the communication power and latency during the mapping process. However, the designed algorithm failed to consider the network throughput.…”
Section: Related Workmentioning
confidence: 99%
“…Step 7. Update buffalos' exploitation x k (t + 1) (10) Step 8. Update the location of buffalos E k (t + 1) (11) Step 9.…”
Section: Impact Of Roughputmentioning
confidence: 99%
“…e shortage of hydrogen filling pumps is certainly a key hurdle to the implementation of this system, although charging points for BEVs or PHEVs were not frequent even a few decades ago. From the report given by the Department of Energy (DOE) of U.S., it has been identified that the FCV costs greater than the ICE [42,43].…”
Section: Fuel Cell Electric Vehicle (Fcev)mentioning
confidence: 99%
“…The authors proposed an approach to alleviate the adverse impact of surplus solar energy by utilising it for charging the EVs [23]. Khan et al presented a comprehensive review on different methods related to the solar-driven EVCS [19]. Saxena et al introduced a notion of grid-connected solar PV-based charging model to improve the dependability of the system [24].…”
Section: Related Workmentioning
confidence: 99%